2014
DOI: 10.1186/1476-511x-13-174
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Apolipoprotein E genetic polymorphism significance on cardiovascular risk is determined by the presence of Metabolic Syndrome among hypertensive patients

Abstract: BackgroundHypertension has a significant relevance as a cardiovascular risk factor. A consistent increase on world’s Metabolic Syndrome (MetS) incidence has been associated with an epidemic cardiovascular risk in different populations. Dislipidemia plays a major role determining the epidemic CV burden attributed to MetS. Apolipoprotein E (ApoE) is involved on cholesterol and triglycerides metabolism regulation. Once ApoE polymorphism may influence lipid metabolism, it is possible that it brings on individual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…People who have three or more of the criteria listed above are considered to have the syndrome. 4,7,[11][12][13][14] It is possible to detect MS in people with normal BMI and so obesity can be defined as a risk factor, but is not present in all those with the syndrome.…”
Section: The Metabolic Syndromementioning
confidence: 99%
“…People who have three or more of the criteria listed above are considered to have the syndrome. 4,7,[11][12][13][14] It is possible to detect MS in people with normal BMI and so obesity can be defined as a risk factor, but is not present in all those with the syndrome.…”
Section: The Metabolic Syndromementioning
confidence: 99%
“…After filtering by availability and reading, consisting of reading the title, abstract, and keywords of each study, 15 articles were selected (Table 1). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] the remainder were excluded from the analysis, because they were not aligned with the subject of the review or with the inclusion parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The foci of identification of the studies selected were investigations of associations between a given genetic polymorphism of a gene involved in the process of a metabolic pathway and risk factors for MS, such as obesity, dyslipidemia, insulin resistance, and hypertension (Table 2). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The relationship between differences in the polymorphic frequency of genes involved in obesity and MS was analyzed in five studies with samples of adults and adolescents with different population profiles. One of them found that nutritional control and exercise may be more effective at preventing risks associated with MS in individuals with the A allele for polymorphism 48867A> C (Asp358Ala) IL6R (rs2228145).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature and function of the major apolipoproteins are summarized in Table 2. Apolipoproteins are physiologically important and are associated with different diseases (36)(37)(38), but their function has yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%